Contribution to the hydrogeological knowledge of the Cremona aquifer system and to the exploitation of new water resources - Cambi, Costanza; Dragoni, Walter; Passeri, Federico; Valigi, Daniela (Italian journal of engineering geology and environment, 2005)
This paper gives the results of a series of hydrogeological and hydrochemical investigations carried out on the multilayered aquifer system of Cremona – characterized by a fresh water/salt water inter- face 400-500 meters below ground level – where a new well field is to be built east of town (AEM, 2001). The well field project is being carried out by the Municipal Energy Company of Cremona (AEM) and calls for the abandoning of a number of older wells and the building of ten new wells. Up to now four piezometers and two wells have already been drilled, which pump at different levels from aquifers located at different depths. The pumping tests done at the two wells have provided transmissivity ( 10-2 m2/s) and storage coefficient (10-3÷10-5) data for each aquifer horizon. A simplified model of the well field was built, calibrated from the pumping test results. The model was then used to simulate aquifer behavior with the well field completed.The simulation showed that the cones of depression would inter- fere with each other, causing a maximum drawdown of about 4 meters greater than that occurring with only one well in operation, if all the wells exploit only two of the usable aquifer horizons. The hydrochemical analysis revealed the natural presence of ammonia, iron, manganese and arsenic in all the aquifers, confirming the necessity of a water treatment plant. An analysis of both the pumping tests and the simulation results indicate that there is a realistic possibility that the salt/fresh water interface may rise up to the wells, although over a long time period (probably decades). Thus it is advisable that the putting into operation of the well field coincide with further investigations for planning solutions to eliminate the possibility of the rising of this interface.